New insect-resistant variety of maize - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Biotechnology could mean that one day insecticides will be a thing of the past. A gene that confers resistance to harmful insects and parasites is inserted into the DNA of the crop-plant to be protected and thereafter the plant manufactures its own...